2008
DOI: 10.1128/jvi.00597-08
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus Infection Accelerates Type 1 Diabetes in Mice with Established Insulitis

Abstract: Infection modulates type 1 diabetes, a common autoimmune disease characterized by the destruction of insulin-producing islet ␤ cells in the pancreas. Childhood rotavirus infections have been associated with exacerbations in islet autoimmunity. Nonobese diabetic (NOD) mice develop lymphocytic islet infiltration (insulitis) and then clinical diabetes, whereas NOD8.3 TCR mice, transgenic for a T-cell receptor (TCR) specific for an important islet autoantigen, show more rapid diabetes onset. Oral infection of infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
83
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(88 citation statements)
references
References 58 publications
5
83
0
Order By: Relevance
“…Bystander activation might occur independently of pancreatic infection and instead contribute to T cell activation in the PLN [33]. These findings could help explain why virus modulation of diabetes is not always associated with virus presence in the pancreas, and can depend on mouse age at infection [7,16,36]. The requirement for pre-existing autoreactive cells also suggests that bystander activation accelerates disease progression rather than initiating beta cell damage.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…Bystander activation might occur independently of pancreatic infection and instead contribute to T cell activation in the PLN [33]. These findings could help explain why virus modulation of diabetes is not always associated with virus presence in the pancreas, and can depend on mouse age at infection [7,16,36]. The requirement for pre-existing autoreactive cells also suggests that bystander activation accelerates disease progression rather than initiating beta cell damage.…”
Section: Introductionmentioning
confidence: 94%
“…Infection of older NOD mice with established insulitis with the rotavirus strain RRV accelerates diabetes onset [7]. This acceleration is dependent on the presence of insulitis, as diabetes development is delayed or unaffected following RRV infection of infant and young adult NOD mice [98].…”
Section: How Might Bystander Lymphocyte Activation Contribute To Diabmentioning
confidence: 99%
See 2 more Smart Citations
“…In CD, for example, it has been suggested that rotavirus infections can increase the risk of disease [7]. Rotaviruses have also been associated with exacerbation of pancreatic islet autoimmunity in humans and shown to promote insulitis and exacerbate diabetes in NOD mice [71]. HCV has also been associated with CD, CrD and thyroiditis [70,72].…”
mentioning
confidence: 99%